FACTORS AFFECTING AUDIT QUALITY - Selviana Ayu Wulandari; Andreas Bambang Daryatno (Graduate Program of Universitas Tarumanagara, 2026)
The company's financial statements can be used as an overview of the condition of a company, because it shows the results of the company's performance during one period. The financial statements are the basis for internal and external parties of the company to make decisions. In Indonesia, there are several cases that have caused a decrease in audit quality. The audit report must be presented in accordance with applicable standards and the conditions of the company, where the results will be accountable. This study aims to analyse the factors that have an influence on audit quality at KAP in the DKI Jakarta area. The independent variables used in this study are independence, work experience, and audit fees, while the dependent variable used is the dependent variable. The population and sample in this study were 96 auditors working in the DKI Jakarta area. This study used primary data using a questionnaire administered via Google Forms. Respondents responded to questions using a Likert scale. Quantitative research methods and multiple linear regression analysis assisted by using SPSS version 25 which aims to determine the test results in the study. The test results in this study show that the variables of independence, work experience, and audit fees have a positive influence on audit quality.